The Role of Mediating Purchase Intention : Influence Between Brand Image and Social Media on Buying Decision Traveloka Apps in Bekasi City - Juan Carlos, Gerry; Indrianna Meutia, Kardinah; Indra Wahyu Putra, Christophorus; Widjanarko, Wirawan; Hasanuddin, Hasanuddin; Siagian, Rosalina; Sobari, Mohamad (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to study and analyze the influence of brand image and social media on purchasing decisions which are mediated by purchasing interest. This research uses a quantitative design with sample in this study consisted of 105 respondents who were users of the Traveloka application in Bekasi City. This research uses multivariate statistical analysis (SEM) techniques to process research data. This research found that there is an influence of brand image on purchasing decisions, but social media has no influence on purchasing decisions. The same results show that buying interest influences purchasing decisions. Other findings show that brand image influences purchasing decisions through purchasing interest, but other findings show that social media has no influence on purchasing decisions through purchasing interest. This research focuses on the influence of brand image and social media marketing on purchasing decisions which are mediated by purchasing interest. This research also focuses on discussing users of the Traveloka application in Bekasi City to see how the Trevaloka application can be of interest to consumers. Theoretically, this research has an improvement research side where this research model has never been examined before during the researcher's research.